Sputum microbiomic clustering in asthma and chronic obstructive pulmonary disease reveals a Haemophilus‐predominant subgroup. Issue 4 (21st October 2019) - Diver, Sarah; Richardson, Matt; Haldar, Koirobi; Ghebre, Michael A.; Ramsheh, Mohammadali Y.; Bafadhel, Mona; Desai, Dhananjay; Cohen, Emma Suzanne; Newbold, Paul; Rapley, Laura; Rugman, Paul; Pavord, Ian D.; et al.
Abstract: Background: Airway ecology is altered in asthma and chronic obstructive pulmonary disease (COPD). Anti‐microbial interventions might have benefit in subgroups of airway disease. Differences in sputum microbial profiles at acute exacerbation of airways disease are reflected by the γProteobacteria:Firmicutes (γP:F) ratio. We hypothesized that sputum microbiomic clusters exist in stable airways disease, which can be differentiated by the sputum γP:F ratio. Methods: Sputum samples were collected from 63 subjects with severe asthma and 78 subjects with moderate‐to‐severe COPD in a prospective single centre trial. Microbial profiles were obtained through 16S rRNA gene sequencing. Topological data analysis was used to visualize the data set and cluster analysis performed at genus level. Clinical characteristics and sputum inflammatory mediators were compared across the clusters. Results: Two ecological clusters were identified across the combined airways disease population. The smaller cluster was predominantly COPD and was characterized by dominance of Haemophilus at genus level (n = 20), high γP:F ratio, increased H influenzae, low diversity measures and increased pro‐inflammatory mediators when compared to the larger Haemophilus ‐low cluster (n = 121), in which Streptococcus demonstrated the highest relative abundance at the genus level. Similar clusters were identified within disease groups individually and the γP:F ratio consistently differentiated between clusters. Conclusion: Cluster analysis by airway ecology of asthma and COPD in stable state identified two subgroups differentiated according to dominance of Haemophilus . The γP:F ratio was able to distinguish the Haemophilus ‐high versus Haemophilus ‐low subgroups, whether the Haemophilus‐ high group might benefit from treatment strategies to modulate the airway ecology warrants further investigation. Abstract : Sputum microbiomic cluster analysis and TDA demonstrates 2 subgroups of stable severe asthma and moderate‐to‐severe COPD differentiated according to dominance of Haemophilus. The Haemophilus ‐high group had no defining clinical characteristics but had lower microbial diversity and increased levels of sputum TNFα and IL1β. γProteobacteria:Firmicutes (γP:F) differentiated the clusters and was the most predictive biomarker of the Haemophilus ‐high group.